Metataxonomic Characterization of Enriched Consortia Derived from Oil Spill-Contaminated Sites in Guimaras, Philippines, Reveals Major Role of Klebsiella sp. in Hydrocarbon Degradation - Kiara Nicole D. Rodriguez; Russel T. Santos; Michael Joseph M. Nagpala; Rina B. Opulencia (International Journal of Microbiology)
Oil spills are major anthropogenic disasters that cause serious harm to marine environments. In the Philippines, traditional methods of rehabilitating oil-polluted areas were proven to be less efficient and cause further damage to the environment. Microbial degradation has poised itself to be a promising alternative to those traditional methods in remediating oil spills. Hence, the present study aimed to enrich and characterize hydrocarbon-degrading microbial consortia from oil-contaminated regions in Guimaras Island for potential use in bioremediation. A total of 75 soil samples were obtained and used as inoculum for the enrichment for hydrocarbon degraders. Afterwards, 32 consortia were recovered and subjected to the 2,6-DCPIP assay for biodegradation ability on four types of hydrocarbons: diesel, xylene, hexane, and hexadecane. The consortia that obtained the highest percent degradation for each of the four hydrocarbons were “B2” (92.34% diesel degraded), “A5” (85.55% hexadecane degraded), “B1” (74.33% hexane degraded), and “B7” (63.38% xylene degraded). Illumina MiSeq 16S rRNA gene amplicon sequencing revealed that the dominant phyla in all consortia are Pseudomonadota (previously Proteobacteria), followed by Bacillota (previously Firmicutes). Overall, the amplicon sequence variants (ASVs) retrieved were mainly from the Gammaproteobacteria class, in which many hydrocarbon-degrading bacteria are found. Predictive functional profiling of the consortium showed the presence of genes involved in the degradation of recalcitrant hydrocarbon pollutants. Fatty acid metabolism, which includes alkB (alkane-1-monooxygenase) and genes for beta oxidation, was inferred to be the most abundant amongst all hydrocarbon degradation pathways. Klebsiella sp. is the predominant ASV in all the sequenced consortia as well as the major contributor of hydrocarbon degradation genes. The findings of the study can serve as groundwork for the development of hydrocarbon-degrading bacterial consortia for the bioremediation of oil spill-affected areas in the Philippines. Likewise, this paper provides a basis for further investigation into the role of Klebsiella sp. in the bioremediation of hydrocarbon pollutants.